REDD+: An Analysis of Initiatives in East Africa Amidst Increasing Deforestation - Bamwesigye, Dastan; Doli, Azdren; Hlavackova, Petra (European Journal of Sustainable Development, 2020)
The study reviewed and examined reducing emissions from deforestation and forest degradation (REDD+) in East Africa. At the helm of Deforestation at its biting implication by the early 2000s, REDD+ was first suggested as a prospective climate change moderation arrangement in 2005 at the United Nations Convention on Climate Change (UNCCC) at the CoP11 in Canada. The basic idea herein was to reduce the increasing loss of forests due to deforestation as well as mitigate climate change as signs were vivid at the time. REDD+ would introduce initiatives to sustain carbon distribution, biodiversity, and stakeholder livelihoods. Developed countries lead in the support of these efforts. Using Literature review and content analysis approaches, the study investigates REDD+ projects in East Africa; Uganda, Rwanda, Kenya, and Tanzania. A considerable level of work has been done as per the findings. However, a lot needs to be put in place since East Africa solely depends on wood biomass for household fuel which is a major cause of deforestation and forest degradation. Keywords: afforestation, alternatives, climate change, deforestation, East Africa, emission control, re-afforestation, REED+, wood fuel